Mobile courseware Physics learning (Chapter 4: Electronic) for SPM students using user-centered design / Mohd Efriezal Zainal Abidin - Zainal Abidin, Mohd Efriezal (2015)
Education is a very powerful subject in our life and this matter need to be prioritized. It contributes to country development and its economic growth. In Malaysia, secondary level of education is one of the crucial parts of youth education which will lead them to the tertiary level of education. In secondary education level, most of the SPM students that take Physics subject have difficulty in understanding the science subject as they cannot imagine and experienced the physics concept through current learning method. The current method that uses a textbook as learning material do not attract the students to Physics because it is boring and does not have an illustration of the physical natural phenomena. Implementation of IT in learning lead to the development of computer aided learning (CAL). Interactive multimedia is said as an effective learning tool and can improve the quality of knowledge. Besides, a combination of courseware and mobile application that has been a trend in today’s modern life will increase the mobility of the learning tools. Suitable approach will be the guidelines in developing the courseware. An evaluation on the usability and learning effectiveness of the courseware will be done at the end of this project.